GENERALIZATION OF THE CRITERIA OF ESTABLISHING THE COMPOSITION OF THE INHERITANCE - Гелич, Алла Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
Summarized criteria for establishment of the inheritance composition In this article examines the heritage of as the object of the relations of the inheritance and defined generalized criteria of the establish of its composition.